Hippocampal but not amygdalar volume loss in narcolepsy with cataplexy - Nemcova, Veronika; Krasensky, Jan; Kemlink, David; Petrovicky, Pavel; Vaneckova, Manuela; Seidl, Zdenek; Rulseh, Aaron; Buskova, Jitka; Susta, Marek; Sonka, Karel (Neuro endocrinology letters, 2015)
OBJECTIVE: Narcolepsy with cataplexy (NC) and narcolepsy without cataplexy (NwoC) are lifelong neurological disorders characterized primarily by excessive daytime sleepiness. Emotional events such as laughter are a trigger of cataplexy in NC. METHODS: We compared the volumes of key limbic structures, the amygdala and hippocampus, in 53 NC, 23 NwoC and 37 control subjects. MRI volumetry was performed in FreeSurfer (FS) and by manual delineation. RESULTS: We found no differences in amygdalar volume in the three groups, however, hippocampal volume was significantly smaller in the NC group than in other groups. Amygdalar and hippocampal volumes assessed by FS were significantly greater, but strong positive correlation between manual and FS results were observed. Thus, both methods are suitable for amygdalar and hippocampal volumetry.